Effect of Bipolar Radiofrequency Energy on Canine Stifle Joint Fluid Temperature - Aoki, Koji; Waldner, Cheryl L.; Sathya, Suresh; Shmon, Cindy (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The aim of this study was to evaluate the effect of bipolar radiofrequency (RF) energy on canine stifle joint fluid temperature.Materials and Methods A standard stifle arthroscopy was performed on 15 canine large breed cadaveric stifle joints. A bipolar RF (VAPR III, 2.3-mm side effect electrode; Depuy Mitek, Raynham, Massachusetts, United States) unit was activated in the joint (1) with or without direct tissue contact, (2) with or without additional 18-gauge needle outflow and (3) for 15 and 30 seconds. The joint fluid temperature was monitored with two fibre optic intra-articular sensors.Results The stifle joint fluid temperature was significantly higher when there was no contact between the tissue and RF probe (mean: 58.6°C with 95% confidence interval [CI]: 53.3–64.0°C) compared with when tissue was contacted (mean: 29.0°C with 95% CI: 26.3–31.6°C). An 18-gauge egress needle had minimal effect on reducing joint fluid temperature. The temperature was higher during the 30-second application of RF energy than the 15-second group.Clinical Significance Bipolar RF energy without firm tissue contact rapidly and significantly increased joint fluid temperature beyond the level reported to damage chondrocytes (above 45°C). Caution is required in the use of bipolar RF energy in the canine stifle joint.
Keywords: stifle joint; arthroscopy; radiofrequency energy; temperature; articular cartilage